Sostenibilidad y contabilidad ambiental: Análisis bibliométrico y revisión documental de la investigación científica en el periodo 2013-2017 (2019)
The work aims to describe the main bibliographic characteristics of world scientific production related to sustainability and environmental accounting (hereinafter CA) in the fields of administration, business and accounting, based on a descriptive analysis of the quantitative evolution of publications , methodological approaches, study units, thematic clusters, countries, main authors and scientific journals with related publications. The methodology corresponds to a descriptive documentary study, reflective of literature, based on the publications of Scopus indexed scientific documents by Elsevier and the use of VOSviewer software. The texts were selected based on various criteria including as keywords "sustainability" and "environment accounting", limitedin the field of "Business, Management and Accounting", during the period between 2013 and 2017. The results identified 66 texts, identifying how the years with the highest number of publications correspond to 2013 with 25.8% and 2017 with 19.7% of the total documents. Likewise, the research approaches applied in the field of sustainability and CA are oriented from the qualitative paradigm with 64%, and quantitative 33%. The types of studies, with greater application are exploratory investigations with 70%,descriptive 20% and correlational with 8%. Regarding the units studied, the documents are focused from research in companies, with 68%, distributed in 77% large companies and 33% small and medium. The most relevant sectors focus on the tertiary sector with 44%, secondary 33% and primary 3%; The countries with the highest number of studies are the United States, United Kingdom, Australia and Italy. Finally, the limitations of the study focus on the methodological strategy proposed by the author, taking intoaccount a single Scopus database. There are some studies that generate contributions without being indexed in the database.